Cuffless blood pressure measuring devices: review and statement by the European Society of Hypertension Working Group on Blood Pressure Monitoring and Cardiovascular Variability - Stergiou, GS; Mukkamala, R; Avolio, A; Kyriakoulis, KG; Mieke, S; Murray, A; Parati, G; Schutte, AE; Sharman, JE; Asmar, R; De La Sierra, A; Asayama, K; et al. (Lippincott, Williams and Wilkins, 2022)
Background: Many cuffless blood pressure (BP) measuring devices are currently on the market claiming that they provide accurate BP measurements. These technologies have considerable potential to improve the awareness, treatment, and management of hypertension. However, recent guidelines by the European Society of Hypertension do not recommend cuffless devices for the diagnosis and management of hypertension.